Protective effects of vitamin e in experimentally induced rhabdomyolysis - Javad Tajik; Reza Kheirandish; Hamideh Rohani; Shima Abbasi (Eurasian Journal of Veterinary Sciences)
Aim: Evaluation of the protective effects of vitamin E administration in a rat model of rhabdomyolysis. Material and Method: Twenty one rats were divided to three equal groups; control (Group 1), glycerol (50% glycerol, 7 mL/kg, IM) and glycerol (50% glycerol, 7 mL/kg, IM) + Vitamin E (100 mg/kg, IP, SID). Ninety-six hours after glycerol injection, blood samples were collected. Serum creatinine, blood urea nitrogen, creatine kinase, aspartate aminotransferase, alanine aminotransferase and lactate dehydrogenase levels were measured. Histopathologic pattern of hepatic and renal tissue damages was also evaluated. Results: Glycerol + vitamin E groups had lower (P<0.05) creatinine, lactate dehydrogenase and creatine kinase levels than the glycerol group, and the administration of vitamin E caused lesser renal tubular damages in glycerol + vitamin E group rather than in glycerol group. Conclusions: Vitamin E administration may decrease the muscle injury and renal damage in rhabdomyolysis cases.